Assessment of Pediatricians' and General Practitioners' Knowledge and Practice Regarding Oral Health, Dental Caries and Its Prevention in Children: A Cross-Sectional Study - Antonija Tadin; Karmela Dzaja (MDPI AG, 2023)
Objectives: This study aimed to evaluate and compare the knowledge and practices of family physicians (general practitioners) and pediatricians concerning children's oral health. Materials and Methods: This research involved a cross-sectional survey with 446 respondents, consisting of 77.8% women and 22.1% men, with 81.6% being general (family) practitioners and 18.4% pediatricians. The survey comprised five sections, gathering information on participants' sociodemographic characteristics, routine oral cavity examination in clinical practice, knowledge about dental caries and its prevention, teething symptoms, and alternatives to fluorides for preventing dental caries. Results: The findings revealed an overall poor understanding of dental caries and its prevention, with an average score of 5.1 ± 1.6 out of a possible 10 points. Notably, practitioners with fewer pediatric patients during the workday, no training on oral health, and uncertainty about physicians' active role in oral health prevention exhibited lower knowledge levels (p ˂ 0.05). Over 90% of participants conducted dental and oral mucosal examinations on their patients. About 25% had received continuing education on children's oral health, and 70.6% expressed interest in further education on the subject. Conclusions: This study highlights insufficient knowledge among physicians regarding dental caries and its prevention. With most participants eager to learn and actively promote children's oral health, providing training is essential to boost their knowledge and support children's oral health.